Motivation, goal-setting, and organizational performance: a case study from uzbekistan’s chemical industry - Mamataliev , Anvar; Urinov, Bobur (GREEN ECONOMY AND DEVELOPMENT, 2025)
This article explores the relationship between employee motivation, goal-setting practices, and organizational performance through a case study of “Merit Chemicals,” a company operating in Uzbekistan’s chemical sector. The findings indicate that clearly defined goals, frequent managerial communication, and positive reinforcement significantly enhance employee motivation. Departments with structured motivational policies and performance-linked objectives demonstrated higher productivity, faster inventory turnover, and improved task completion rates. The study applies goal-setting theory to the context of a post-Soviet industrial environment and highlights the managerial implications of motivational practices on firm performance. The article offers actionable recommendations for corporate leaders and policymakers seeking to boost productivity through behavioral strategies.